Penyuluhan Kesehatan Reproduksi Diet Vitamin D pada Remaja Putri di Kota Palembang dengan Dismenore Primer - Sepiwiryanti, Wika; Legiran, Legiran; Wardiansah, Wardiansah; Effendi, Kms. Yusuf; Sari, Bunga Anggreini; Ramdiana, Ramdiana (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Primary dysmenorrhea is the most frequent gynecological issue in women of reproductive age. Various therapeutic approaches have been used to treat dysmenorrhea, such as psychotherapy, administration of non-steroidal anti-inflammatory drugs, oral contraceptive pills, and others. However, these drugs often have undesirable side effects. Therefore, other alternatives, such as herbal medicine, diet, supplements, vitamins, and minerals, are important concerns. Vitamin D, also known as calciferol, is believed to regulate cell growth and apoptosis and modulate the immune system and other functions. The active type of vitamin D has the potential to decrease prostaglandin production within the endometrium and restrict its biological impact by influencing prostaglandin receptors. Moreover, it can prompt anti-inflammatory responses through diverse pathways. Vitamin D is naturally synthesized in the skin when exposed to sunlight's ultraviolet B (UVB) radiation, but it can also be acquired from dietary sources and supplements. This community service aims to educate young women about dysmenorrhea by increasing participation in counseling. The activity method used was counseling aimed at young female students at STIKES Abdurahman in Palembang, with a total of 120 participants, and this counseling activity was carried out for 150 minutes. From the results of this community service, the students understand the importance of maintaining reproductive health. They can overcome primary dysmenorrhea by adjusting a diet that contains vitamin D.